Association between the ERCC5 Asp1104His Polymorphism and Cancer Risk: A Meta-Analysis - Zhu, Mei-Ling; Wang, Mengyun; Cao, Zhi-Gang; He, Jing; Shi, Ting-Yan; Xia, Kai-Qin; Qiu, Li-Xin; Wei, Qing-Yi (PloS one, 2012)
Excision repair cross complementing group 5 (ERCC5 or XPG) plays an important role in regulating DNA excision repair, removal of bulky lesions caused by environmental chemicals or UV light. Mutations in this gene cause a rare autosomal recessive syndrome, and its functional single nucleotide polymorphisms (SNPs) may alter DNA repair capacity phenotype and cancer risk. However, a series of epidemiological studies on the association between the ERCC5 Asp1104His polymorphism (rs17655, G>C) and cancer susceptibility generated conflicting results. To derive a more precise estimation of the association between the ERCC5 Asp1104His polymorphism and overall cancer risk, we performed a meta-analysis of 44 published case-control studies, in which a total of 23,490 cases and 27,168 controls were included. To provide additional biological plausibility, we also assessed the genotype-gene expression correlation from the HapMap phase II release 23 data with 270 individuals from 4 ethnic populations. When all studies were pooled, we found no statistical evidence for a significantly increased cancer risk in the recessive genetic models (His/His vs. Asp/Asp: OR = 0.99, 95% CI: 0.92-1.06, P = 0.242 for heterogeneity or His/His vs. Asp/His + Asp/Asp: OR = 0.98, 95% CI: 0.93-1.03, P = 0.260 for heterogeneity), nor in further stratified analyses by cancer type, ethnicity, source of controls and sample size. In the genotype-phenotype correlation analysis from 270 individuals, we consistently found no significant correlation of the Asp1104His polymorphism with ERCC5 mRNA expression. This meta-analysis suggests that it is unlikely that the ERCC5 Asp1104His polymorphism may contribute to individual susceptibility to cancer risk.